Sistem informasi manajemen ticketing event dengan payment gateway berbasis Node.js dan Next.js - Prasetyo, Ari Yogi; Swalaganata, Galandaru (Universitas Merdeka Malang, 2024)
FTI Fest is a music concert event organized by one of the faculties at Merdeka University Malang. In its management, the FTI Fest event still uses various manual methods and tends to be less effective in carrying out transaction processes, especially in terms of ticket sales. Therefore, a management information system is needed that is tailored to your needs to make ticket ordering easier. This research aims to design and develop an event ticketing management information system using the waterfall method. The research stages were carried out starting from system requirements analysis, system design, implementation, system testing, to maintenance. The results of functionality testing show that the system functions well and is suitable for use. The information system developed in this research can make it easier for admins or event managers to manage events and tickets and simplify the process of recording transactions. Apart from that, with a payment gateway, buyers can make event ticket purchase transactions anywhere and anytime.